2017
DOI: 10.1063/1.4998806
|View full text |Cite
|
Sign up to set email alerts
|

Electric potential profile created by end electrodes in a magnetized rf discharge plasma

Abstract: The problem of generating a stationary electric field in a magnetized radio-frequency discharge (rf) plasma is studied experimentally. Helmholtz coils produce magnetic field in a cylindrical vacuum chamber with diameter of 85.6 cm and length of 220 cm. RF discharge is generated at a frequency of ∼ 5 MHz. The rf power absorbed by plasma lies in the range 0.5-1.5 kW. Electrodes defining a negative potential are placed at the ends of the chamber. Two pairs of circular flat electrodes with diameter of 5.5 and 45 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It can decrease by 2 orders of magnitude over several centimetres (Liziakin et al. 2017), and replacing such a profile with a uniform one can significantly distort the real picture. The good agreement between the calculated profiles and the experiment in the current study is largely due to the fact that the density profile in the experiment was quite flat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can decrease by 2 orders of magnitude over several centimetres (Liziakin et al. 2017), and replacing such a profile with a uniform one can significantly distort the real picture. The good agreement between the calculated profiles and the experiment in the current study is largely due to the fact that the density profile in the experiment was quite flat.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to distinguish between cases when the negative potential (Liziakin et al. 2017) (relative to the outer cylindrical surface) and the positive one (Shinohara & Horii 2007) are maintained on the cylinder axis. The difference between these cases consists primarily of the difference between the areas of the negative and positive electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar configuration, negative electric fields were produced with localised negative bias using emissive electrodes 86 . Recently, Liziakin et al showed that end-electrodes effectiveness to affect the potential increased with the electrodes' area, both in reflex 95 and RF 96 discharges.…”
Section: A Foundations For Driving Crossed-field Flows Via Electrode ...mentioning
confidence: 99%
“…In such configuration, the entire plasma starts rotation [46,47]. There are two types of systems: systems in which the end electrodes participate in the process of maintaining the discharge and systems in which the discharge is created by an external source of energy [48,49]. The connection between the discharge parameters and the plasma potential on the axis in such a system was shown in experiments with a reflex discharge [50] and in the theoretical research [51].…”
Section: Introductionmentioning
confidence: 99%